Characteristics of the Level of the Phisical Health and Physican Fitness of the Medicos Subject to the Somatotype by Properly Sized Variation Level - E. M. Kalmykova; E. V. Harlamov (Медицинский вестник Юга России, 2011)
Purpose: Statement of physical fitness and physical health of the medicos subject to the somatotype by the properly sized variation level.Materials and Methods: 513 3d year medicos (140 youths and 373 girls), aged 17–21 years old, and having different level of physical fitness, were examined. The examination was carried out on the disease nosology of the students, (according to the international disease classification). Physical fitness level was stated by the results standards of the standart test exercises, used in training and test classes at the Department. The observations were carried out during 4 terms and recorded in the register. An average grade was stated, permitting to judge about the development level of the motion qualities. Somatotyping was carried out.Results: During the 4 terms an objective increase of physical fitness rates was observed both for healthy people and ones with deviations in the level of health.Summary: The representatives of MeС type (youths) and МеМаС type (girls) tested the most physically fitted.